Integrating public health and sport management: Sport participation trends 2001–2010. Issue 2 (May 2015) - Eime, R.M.; Sawyer, N.; Harvey, J.T.; Casey, M.M.; Westerbeek, H.; Payne, W.R.
Highlights We examine ten year sport and recreation participation levels and trends. Participation in general levels of leisure time physical activity increased. Organised and/or club based participation remained steady over the decade. There is a need for improved sport participation data to inform policy development.